2016
DOI: 10.1016/j.bbamcr.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 intracellular domain negatively regulates PAK1 signaling pathway through direct interaction

Abstract: p21-Activated kinase 1 (PAK1) is a serine/threonine protein kinase implicated in cytoskeletal remodeling and cell motility. Recent studies have shown that it also promotes cell proliferation, regulates apoptosis, and increases cell transformation and invasion. In this study, we showed that NOTCH1 intracellular domain (NOTCH1-IC) negatively regulated PAK1 signaling pathway. We found a novel interaction between NOTCH1-IC and PAK1. Overexpression of NOTCH1-IC decreased PAK1-induced integrin-linked kinase 1 (ILK1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…p21-activated kinase 1 (PAK1) was first found as a member of the Pak family (4). Initially, it was cloned from cerebral tissues as p21 kinase (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…p21-activated kinase 1 (PAK1) was first found as a member of the Pak family (4). Initially, it was cloned from cerebral tissues as p21 kinase (4).…”
Section: Introductionmentioning
confidence: 99%
“…p21-activated kinase 1 (PAK1) was first found as a member of the Pak family (4). Initially, it was cloned from cerebral tissues as p21 kinase (4). Members of the Pak family play an essential role in immune escape, motility, angiogenesis and genetic regulation (5).…”
Section: Introductionmentioning
confidence: 99%
“…The direct association of PAK1 and Notch1 already has been shown, interestingly indicating regulation of PAK1 activity via NICD. 65 Furthermore, Vadlamudi et al 66 showed that phosphorylation of SMRT/ HDAC1 Associated Repressor Protein (SHARP) via PAK1 resulted in repression of Notch target genes. In addition, implications for PAKs inducing a stem cell phenotype already have been made in renal cell carcinoma and in vitro using CRC and pancreatic cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal inflammation results in PAK1 overexpression, thereby tightly controlling the release of Notch1 and bcatenin upon activation and maintaining proper stem cell proliferation and differentiation. 15,65 Loss of PAK1 in this setting leads to diminished differentiation and a more stem cell-like intestinal phenotype as shown by Notch1, OLFM4, LGR5, and Wnt/b-catenin activation, and overexpression with an increase in tumorigenesis (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…ILK, which plays an essential role in tumorigenesis, has been shown to regulate OPC proliferation and differentiation (Hussain & Macklin, 2017). In addition to ILK, NICD is also reported to interact directly with PAK1 and facilitate PAK1 (and/or ILK) nuclear translocation (Yoon et al ., 2016). HDAC, histone deacetylase; NCoR, nuclear receptor co‐repressor 2; RBP‐J, recombination signal binding protein for immunoglobulin kappa J region.…”
Section: Group I Paks and Oligodendrocyte Developmentmentioning
confidence: 99%